Perancangan Alat Bantu Perakitan Spring Bed yang Ergonomi Berdasarkan Analisa RULA dan REBA - Anwardi, Anwardi; Nofirza, Nofirza; Vilhelmina, Vira; Anggraini, Wresni; Silvia, Silvia (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2021)
CV. XYZis an industry engaged in the field of furniture producing spring bed, cabinets, buffets, chairs and others. At the spring bed assembly station, the worker assembles a springbed frame on the floor with a work position bent, squatting or sitting up to form a working posture with angles of 450 to 700 and does not use tools to support ergonomic position and posture. The purpose of this study was to design an ergonomic tools for conducted work activities on the skeleton spring bedassembly station use the RULA-REBA methods. The method of research is done by compared scores and levels before and after assembly tool design. The results show that REBA score is at 9/11 level and RULA is at 7/7 level which means that the current working condition must be improved and very unsafe for workers. After assembling the assembly tool use SolidWork software with dimension size is determined based on anthropometry data, where the height is 102 cm, length 204 cm, and width 134 cm. Then simulated use ErgoFellow 2.0 software, obtained REBA 4 and 5 score from 11 total level and RULA score is 3/7 level which means the risk of injury to worker in assembly station of skeleton of springbed can be minimized.